Stek Tumbuhan Kebiul (Caesalpinia sp.) Berbantuan Air Kelapa sebagai Hormon Pertumbuhan Alami - Ika Saputri; Deni Parlindungan; Reti Novianti; Widia Gusti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Caesalpinia sp. is a popular traditional medicinal plant in Bengkulu, but people have not cultivated it and still harvest it from nature. Efforts towards cultivation must begin before these plants are rare because in nature will run out. In this study measure the growth of Kebiul plant cuttings with the help of natural hormones from 3 variants of coconut water consist of: young, medium and old coconut water, which will be compared with synthetic growth regulators (rootone-F) and controls (without treatment). The study was carried out for six weeks with twelve observations, measurements were made in the afternoon, with the parameters of observing the shoots (the growth number, growth time, growth rate), shoots number and leaves number.The results showed that the percentage of the number of seedlings growing was (P3:41.67%; P1:33.33%; P2:25%; P4: 16.67%; P5: 8.33%), Growing time (days) namely (P5: 23; P1: 23.25; P3: 23.29; P2: 24.25; P4: 40.5), Growth rate (P2: 0.81; P3: 0.59; P5: 0.18; P1: 0.12; P4: 0.04 ), Average number of shoots (P3: 1.4; P2: 1.3; P1: 1; P4: 1; P5: 1), and Average number of leaves (P2: 2.67; P3: 1, 92; P1:0; P4:0; P5:0).The use of coconut water on Kebiul plant cuttings, with the best results sequentially P3 (young coconut water), P2 (medium coconut water), and P1 (old coconut water).